SQL Server 2005 T-SQL Recipes A Problem-Solution Approach - Sack, Joseph (Apress : Imprint: Apress, 2006)
Need to brush up on specific SQL Server tasks, procedures, or Transact-SQL commands? Not finding what you need from SQL Server books online? Or perhaps you just want to familiarize yourself with the practical application of new T-SQL related features. SQL Server 2005 T-SQL Recipes: A Problem-Solution Approach is an ideal book, whatever your level as a database administrator or developer. This no-fluff desk reference offers direct access to the information you need to get the job done. It covers basic T-SQL data manipulation, the use of stored procedures, triggers and UDFs, and advanced T-SQL techniques for database security and maintenance. It also provides hundreds of practical recipes that describe the utilities of features and functions, with a minimim of background theory. Additionally, this book provides how-to answers to common SQL Server T-SQL questions, conceptual overviews, and highlights of new features introduced in SQL Server 2005. It also features concise T-SQL syntax examples, and you can use the book to prepare for a SQL Server-related job interview or certification test.